2002
DOI: 10.1080/13102818.2002.10819155
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Aphid Transmissibility of Plum Pox Virus Isolates

Abstract: The aphid transmissibility of seven Plum pox virus (P PV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Two viral proteins, CP and HCPro, have been shown to be involved in aphid transmission of number of potyviruses, and defects in either protein have been proved to abolish it (76). Aphid transmission of seven PPV isolates, including four Bulgarian isolates (one apricot, one plum and two peach) with M. persicae to N. benthamiana plants has been studied (45). Transmission rates of 30 and 26% have been found for the apricot (PPV-A) and the plum (PPV-P) isolates, respectively, while both peach isolates (PPV-P45 and PPV-P48) and the other three isolates have failed to be aphid transmitted.…”
Section: Transmissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two viral proteins, CP and HCPro, have been shown to be involved in aphid transmission of number of potyviruses, and defects in either protein have been proved to abolish it (76). Aphid transmission of seven PPV isolates, including four Bulgarian isolates (one apricot, one plum and two peach) with M. persicae to N. benthamiana plants has been studied (45). Transmission rates of 30 and 26% have been found for the apricot (PPV-A) and the plum (PPV-P) isolates, respectively, while both peach isolates (PPV-P45 and PPV-P48) and the other three isolates have failed to be aphid transmitted.…”
Section: Transmissionmentioning
confidence: 99%
“…Helper components with Mr. of 52 kDA have been successfully purified from N. benthamiana plants inoculated with both types of isolates (aphid and nonaphid transmitted). The authors have shown that the helper components of two of non-transmissible isolates with defective CPs (deletions and DAG substitutions to DAL and NAG) have mediated aphid transmission of non CP defective isolates, thus proving that the CP defects rather than the HPs have been the reason for their non transmission by aphids (45).…”
Section: Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies on the molecular epidemiology of PPV have aimed to identify viral genomic signatures explaining biological features of the virus (Bousalem et al , ; Dallot et al , ; Glasa et al , , , ; Maejima et al , ; Schneider et al , ; Chirkov et al , ). However, identification of such genomic determinants at the single amino acid level has been unsuccessful owing to the high sequence divergence among strains (Salvador et al , ), even among populations or isolates within a single strain (except for certain obvious point mutations associated with aphid transmissibility) (Maiss et al , ; Kamenova et al , ; Glasa et al , ). In the current study, we demonstrate for the first time that the specific amino acid residue under positive selection determines intra‐strain biological variation in PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed intra‐strain variation in biological properties, such as host preference (Maiss et al , ; Dallot et al , ), aphid transmissibility (Deborre et al ., ; Glasa et al , ; Schneider et al , ), and competitiveness (Glasa et al , ), among PPV isolates. Although these intra‐strain biological variations are believed to be due to viral genetic diversity (James et al , ), existing studies have not elucidated the correlations among them based on genome sequences of PPV isolates, with the exception of certain non‐aphid‐transmissible isolates with mutations in the Pro‐Thr‐Leu (PTK) and Asp‐Ala‐Gly (DAG) motifs, which are responsible for aphid transmission of potyvirus (Atreya et al , ; Peng et al , ) in the helper component proteinase (HC‐Pro) (Glasa et al , ) and coat protein (CP) (Maiss et al , ; Kamenova et al , ), respectively. Therefore, it has been suggested that biological information for a range of isolates from each PPV strain is unlikely to be available in the immediate future (Candresse and Cambra, ).…”
Section: Introductionmentioning
confidence: 99%